Efforts to maintain Latvian identity in Augšbebri village, Omsk region - Antiņa, Ināra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Driven by various motives, Latvian emigrants and exiles have been voluntarily or involuntarily choosing various regions of the world as their new home. Siberia is one such region – the first Latvian exiles were deported to this remote Russian territory already in the 18th century and a new wave of settlers moved there on their own accord in search of a better life in the early 19th century. Some of the Latvian villages have survived in Russia to this day. Augšbebri (Bobrovka) village in the Tara district, Omsk region, is one of them. Augšbebri village was founded in 1897 when the first settlers from Latvia registered as residents there. The modern-day residents of Augšbebri are the sixth generation of ethnic Latvians living in Siberia. The villagers have preserved their Latvian language skills and traditions, but are concerned about the younger generation’s ability to maintain their Latvian identity, because only few young people use Latvian in their day-to-day communication. The villagers’ efforts to maintain their language skills, traditions and Latvian identity in their adopted homeland are especially admirable at a time when so many Latvians leave their native country and establish Latvian communities in foreign countries in attempts to preserve their identity.